Isolation, probiotic characterization and whole-genome sequencing of gut Faecalibacterium prausnitzii - Xuemei Sun; Ziyi Zhang; Jielun Hu (Human Nutrition & Metabolism)
The next generation of probiotics Faecalibacterium prausnitzii is a very important butyric acid producing bacterium in the human intestinal tract, but its extreme sensitization to oxygen hinders its isolation for further study and application. The current study attempted to isolate and identify F. prausnitzii strains from human feces, as well as sequencing the whole genomes, to study their basic characteristics and probiotic potentials. Two strains were successfully obtained named F. prausnitzii 20 and F. prausnitzii 28, which entered the logarithmic growth phase at 24 h and then the stable growth phase at 48 h. At 72 h, F. prausnitzii 28 grew better and resulted a lower pH in culture medium than F. prausnitzii 20. The butyric acid production of F. prausnitzii 28 was up to 38.68 mmol/L. The two strains were tolerant to pH 3.0 and 0.3 % of bile salt, and were capable of growing on glucose, inulin, β-glucan, and konjac glucomannan as the sole carbon source, but not on pectin, arabinogalactan, and arabinoxylan. Additionally, they exhibited good inhibitory activity against α-glucosidase and α-amylase, with inhibition rates of up to 60.90 % and 32.69 %, respectively, as well as strong scavenging abilities for DPPH, ABTS, and superoxide anion free radicals (91.92 %, 73.06 %, and 95.82 %, respectively). The whole genome of F. prausnitzii 28 had a size of 3,950,000 bp with a GC ratio of 56.50 % and possessed 2752 genes consisting of 2645 coding sequences and 107 non-coding sequences. Gene prediction confirmed that F. prausnitzii 28 had acid resistance, bile salt resistance, oxidation resistance and adhesion properties. This study provided new strains for the study of F. prausnitzii, as well as a theoretical basis for the research and development of F. prausnitzii based therapies in hypoglycemic and other health aspects.